SUBSIDENCE – A MAJOR EFFECT OF COAL MINING IN RANIGANJ COALFIELD - GUPTA, ANUP KRISHNA; DUTTA, AJOY KUMAR; BASU, RITA (IJRDO - Journal of Business Management, 2018)
Coal, the most important fossil fuel in India is vital for industrial growth. It is India's least costsource of primary energy and currently meets two-thirds of the country's energyneeds.The state of   West Bengal has rich deposits of coal and, accounting for about half of India's total Over 240 years coal is being produced from Bengal which has major consequences on the environment.Un-scientific, unsystematic and illegal mining are the primary causes of fires resulting into subsidence in large part of Raniganj coalfield area. Intensive mining activities during the past by over thousand small fragmented mines have created many complexity for future development. Coal, which are left as safety pillars and ribs during the course of extraction (mining) in old workings and abandoned mines, catches fires due to  spontaneous combustion  and  gets   further aggravated due to illegal mining ,resulting into subsidence. Mining-induced subsidence, cause horizontal and vertical movements in the land surface, and open cracks and fissures that serve as inlets for oxygen, which in turn aggravate the problem of coal fires. These inter-related phenomena often render the mining areas unfit for human inhabitationThe population living in the old mining areas has increased many times over the years, though these areas became unsafe for habitation. With gradual industrialisaton in this area ,haphazard and unplanned growth of surface construction have emerged .Over 4400 million tones of valuable coal reserve lie below such townships which will affect  future mining operationThe study is related to Subsidence and its effect occurred due to  coal mining operations in Ranganj Coalfield area for centuries.